Rupture of Brumadinho dam (Minas Gerais, Brazil): embryotoxicity in zebrafish induced by metal mixture-contaminated water - Peixoto, Paloma Vitória Lima [UNESP]; Andrade, Ítalo Bertoni Lopes de [UNESP]; Sales, Bianca Camargo Penteado [UNESP]; Pereira, Lilian Cristina [UNESP] (Taylor & Francis, 2022)
Rupture of dam B-1 at the Córrego do Feijão mine in Brumadinho, state of Minas Gerais, Brazil (25/Jan/2019) contaminated the Paraopeba River with mine waste. To identify the adverse effects of this event on public and environmental health, we conducted the Fish Embryo Acute Toxicity (FET) test (OECD No. 236). During the tests, zebrafish embryos were exposed for 144 hours to solutions containing realistic concentrations of dissolved iron and aluminum and total manganese at the following analysis points upstream or downstream of the dam: 10 km, upstream; 19.7 km, downstream, at the point where water for consumption is collected; 24.5 km, downstream, in the city of Mário Franco; and 59 km, downstream, on the border between the towns of Juatuba and Betim. Metal concentrations were taken from September 2019 report No. 53 released by IGAM. Mortality was high at all exposure points and reached 93% at the Juatuba/Betim point. We also detected lethal, sublethal and teratogenic effects, such as non-hatching, non-inflation of the swim bladder, pericardial edema and scoliosis, affecting up to 25% of embryos at the other analysis points. The results highlight the need for continuous monitoring of the water quality of the Paraopeba River.
Keywords: Brumadinho dam failure; FET test; metals; Paraopeba River; zebrafish